Aromatic and medicinal plants used in traditional medicine in the region of Tiaret, North West of Algeria - Djahafi, Asma; Taibi, Khaled; Ait Abderrahim, Leila (Mediterranean Botany, 2021)
Herbal medicine is gaining an increasing importance in the management of various ailments, but little is known about traditional practices in Algeria. This ethnopharmacological study aims to document medicinal and aromatic plants used in traditional medicine in the region of Tiaret (northwest of Algeria) in order to contribute to safeguard the local pharmacopoeia as cultural heritage, and to provide a scientific basis for developing novel strategies for such practices which can help for drugs discovery. Semi-structured interviews with 64 traditional healers and herbalists were realized in the region of Tiaret (Algeria) throughout field studies achieved from December 2018 to May 2020. Interviews covered sociodemographic information, popular and vernacular names of the medicinal plants, mode of use and toxicity among other data. Results reveal the use of 107 plant species belonging to 45 families and 97 genera for the treatment of various ailments. Lamiaceae, Apiaceae and Asteraceae were the most represented families. The most frequently cited species were Senna alexandrina Mill. (FC=27), Atriplex halimus L. and Bunium incrassatum Amo (FC=23 each), Foeniculum vulgare Mill. (FC=22), and Matricaria chamomilla L. (FC=21). However, the higher use values were reported for Nigella sativa L. (UV=1.5), Trigonella foenum-graecum L. (UV=1.38), Thymus serpyllum L. (UV=1.2), Ziziphus lotus (L.) Lam. (UV=1.14), Urtica dioica L. (1.13), and Senna alexandrina Mill. (UV=0.52) respectively. Interestingly, Bunium incrassatum Amo, Echinops spinosissimus Turra, Cucurbita moschata Duchesne, Pennisetum glaucum (L.) R.Br and Malus domestica Borkh. were reported for the first time as medicinal plants in the north Africa and Algeria. Moreover, 246 new therapeutic uses were described. It should be noted that Pistacia atlantica Desf., Tetraclinis articulata (Vahl) Mast., Oudneya africana R. Br., Euphorbia guyoniana Boiss. & Reut, Teucrium polium L. and Marrubium deserti (Noë) Coss. are endemic to North Africa-Algeria, Northern and Central Sahara. Furthermore, Artemisia herba-alba Asso, Anacyclus pyrethrum (L.) Lag., Cuminum cyminum L., Saussurea costus (Falc.) Lipsch., Boswellia sacra Flueck. and Pistacia atlantica Desf. are considered threatened, rare or endangered species. Our findings are relevant not only for the future studies and experiments in the search for novel compounds, but also for the safeguard of traditional knowledge and biodiversity.